Fiber-Optic Distributed Acoustic Sensing for Smart Grid Application - Xiaofeng Zhang; Jun Qi; Xiao Liang; Zhen Guan; Zeguang Liu; Chang Zhang; Dabin Chen; Weifeng Deng; Changzhi Xu; Xinwei Wang; Huanhuan Liu (Photonics)
Fiber-optic distributed acoustic sensing (DAS) promises great application prospects in smart grids due to its superior capabilities, including resistance to electromagnetic interference, long-distance coverage, high sensitivity and real-time monitoring. In this paper, we review the research progress and application status of DAS technology in power systems, focusing on its applications in areas such as the wind-induced vibration detection of transmission lines, partial discharge monitoring, transformer condition monitoring, and underwater cable and renewable energy transmission monitoring, as well as in the safety and protection of surrounding power facilities. Addressing the challenges currently faced by DAS technology in the smart grid, including detection accuracy, system cost, and data processing capability, this paper analyzes its major technical bottlenecks and proposes future research directions.